Hubungan Tingkat Stress Remaja Dengan Siklus Menstruasi Pada Siswi Kelas XII SMAN 3 Rangkasbitung - Mira Suminar; Dewa Ayu Sri Saraswati; Novi Nurdiani (STIKes IMC Bintaro, 2023)
Introduction : One of the problems faced by many women, especially teenagers, is irregular menstrual cycles. In Indonesia, most of the menstrual problems are irregular at the age of 10-29 years, amounting to 15.2%. One of the causes is the stress factor because cortisol causes hormonal imbalances in the menstrual cycle. Research Objectives: to determine the relationship between adolescent stress levels and the menstrual cycle in class XII students at SMAN 3 Rangkasbitung 2022. Research Methods: Quantitative study with a cross sectional approach. The population in this study were 104 respondents, while the sample was 82 respondents. The sampling technique used is Simple Random Sampling. The research instrument used the DASS Questionnaire 42. Research results: Showed that the majority of respondents experienced a low level of stress that did not affect the normal menstrual cycle as many as 49 female students (94.2%). The results of bivariate analysis with the Chi Square test obtained a p-value of 0.000 (p-value <0.05). Conclusion: It can be concluded that there is a significant relationship between the relationship between adolescent stress levels and the menstrual cycle in class XII students at SMAN 3 Rangkasbitung in 2022. Suggestion: Based on the research results, it is recommended that female students receive education from schools regarding good stress management and reproductive health in order to avoid menstrual cycle disturbances.